Exercise performance and thermoregulatory responses of elite athletes exercising in the heat: Outcomes of the Thermo Tokyo Study - de Korte, J. Q.; Bongers, C. C. W. G.; Hopman, M. T. E.; Eijsvogels, T. M. H. (Sports Medicine, 2021)
Objective: We examined the impact of simulated Tokyo 2020 environmental condition on exercise performance, thermoregulatory responses and thermal perception among Dutch elite athletes. Methods: 105 elite athletes from different sport disciplines performed two exercise tests in simulated control (15.9 ± 1.2 °C, relative humidity (RH) 55 ± 6%) and Tokyo (31.6 ± 1.0 °C, RH 74 ± 5%) environmental conditions. Exercise tests consisted of a 20-min warm-up (70% HRmax), followed by an incremental phase until volitional exhaustion (5% workload increase every 3 min). Gastrointestinal temperature (Tgi), heart rate, exercise performance and thermal perception were measured. Results: Time to exhaustion was 16 ± 8 min shorter in the Tokyo versus the control condition (- 26 ± 11%, whereas peak power output decreased with 0.5 ± 0.3 W/kg (16 ± 7%). Greater exercise-induced increases in Tgi (1.8 ± 0.6 °C vs. 1.5 ± 0.5 °C, p < 0.001) and higher peak Tgi (38.9 ± 0.6 °C vs. 38.7 ± 0.4 °C, p < 0.001) were found in the Tokyo versus control condition. Large interindividual variations in exercise-induced increase in Tgi (range 0.7-3.5 °C) and peak Tgi (range 37.6-40.4 °C) were found in the Tokyo condition, with greater Tgi responses in endurance versus mixed- and skill-trained athletes. Peak thermal sensation and thermal comfort scores deteriorated in the Tokyo condition, with aggravated responses for power versus endurance- and mixed-trained athletes. Conclusion: Large performance losses and Tgi increases were found among elite athletes exercising in simulated Tokyo conditions, with a substantial interindividual variation and significantly different responses across sport disciplines. These findings highlight the importance of an individual approach to optimally prepare athletes for safe and maximal exercise performance during the Tokyo Olympics.